2015
DOI: 10.1186/s12861-015-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

FOXL2 modulates cartilage, skeletal development and IGF1-dependent growth in mice

Abstract: BackgroundHaploinsufficiency of the FOXL2 transcription factor in humans causes Blepharophimosis/Ptosis/Epicanthus Inversus syndrome (BPES), characterized by eyelid anomalies and premature ovarian failure. Mice lacking Foxl2 recapitulate human eyelid/forehead defects and undergo female gonadal dysgenesis. We report here that mice lacking Foxl2 also show defects in postnatal growth and embryonic bone and cartilage formation.MethodsFoxl2−/− male mice at different stages of development have been characterized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Most of the pelvis is formed and grows through a process of intramembranous ossification except the acetabulum, which also grows by endochondral ossification. Thus IGF-1 levels influence the size of the pelvic bones through its effects on ossification [38]. The strength of the association with PC1 was not markedly affected by exclusion of the related Greyhound/Labrador Retriever cross breeds because this association was driven by the dog breeds with lower representation (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the pelvis is formed and grows through a process of intramembranous ossification except the acetabulum, which also grows by endochondral ossification. Thus IGF-1 levels influence the size of the pelvic bones through its effects on ossification [38]. The strength of the association with PC1 was not markedly affected by exclusion of the related Greyhound/Labrador Retriever cross breeds because this association was driven by the dog breeds with lower representation (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…For the super shift experiment, EMSA reactions were pre-incubated for 20 min at room temperature with rabbit anti-HA (Santa Cruz sc805) or rabbit polyclonal anti-FOXL2, raised against residues FRPPPAHFQPGKGLF (Eurogentec s.a., Belgium) within the forkhead DNA binding domain and used after affinity purification; specificity was confirmed by western blotting. This antibody has been extensively used and validated in previous studies (Uda et al, 2004; Marongiu et al, 2010; Marongiu et al, 2015). For competition experiments, a 50- or 100-fold molar excess of unlabeled double-stranded WT oligonucleotide was included in the DNA binding reaction (Supplementary material Fig.…”
Section: Methodsmentioning
confidence: 99%
“…FOXL2 is also implicated as a master transcription factor in a range of developmental pathways that include growth and bone, cartilage and uterine maturation (Shi et al, 2014; Heude et al, 2015; Marongiu et al, 2015; Bellessort et al, 2015). In the pituitary gland, where it has been further analysed, it is expressed mainly in thyreotrope and gonadotrope cells (Ellsworth et al, 2006), and it has been reported that FOXL2 along with SMAD proteins in activin A induction, regulates Fshb expression in gonadotrope cells (Lamba et al, 2009; Tran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Foxl2 deletion in either CNCCs or CMCs prevents eyelid closure and induces subtle skeletal developmental defects [Heude et al, 2015]. In addition, FOXL2 is also involved in cartilage and skeletal formation, bone mineralization, and growth as demonstrated in a constitutive Foxl2 -deficient mice model [Shi et al, 2014;Marongiu et al, 2015].…”
Section: An Introduction To Foxl2: Early Findings the Mammalian Viewmentioning
confidence: 99%